Obesity in rheumatoid arthritis: impact on response to biologic therapies - Zehra Irshad; Nicola J. Gullick (Exploration of Musculoskeletal Diseases)
Background: We performed a service evaluation of local patients with rheumatoid arthritis (RA) treated with biologic or targeted systemic disease-modifying anti-rheumatic drug (b/ts)DMARDs to see if patients who were obese had different outcomes, and whether referral to specialist obesity services was considered. In addition, we undertook a systematic review of the impact of obesity on treatment outcomes in patients with RA receiving biologics. Methods: A retrospective case note review was performed for 220 patients with RA attending clinic on treatment with a (b/ts)DMARD. BMI, DAS28, DAS components and demographics were recorded. Referrals to weight management services were evaluated. A systematic review was performed according to PRISMA guidelines (PROSPERO CRD42023433669). Electronic databases were searched for papers reporting RA patients receiving biologics with clinical responses in patients with and without obesity. Results: Within our service, 24% of patients were obese; 12% were morbidly obese. Patients with obesity had higher disease activity scores. Only 25% of eligible patients were referred to weight management services. 238 records were identified through database searches. 69 full-text records were assessed for eligibility and data extracted from 39 records including 40,445 patients receiving a variety of biologic agents. Reduced responses, remission rates, and drug retention were seen in patients with obesity receiving TNF inhibitors (TNFi), but this was not seen for abatacept, rituximab, or tocilizumab. Discussion: Obesity is common in patients with RA and can be associated with higher disease activity. Patients who are obese are less likely to reach remission with TNFi. The use of non-TNFi biologics should be considered earlier in the treatment pathway alongside holistic approaches to aid lifestyle change for this patient group.